JADID NASRIDA ONA OBRAZINING YETAKCHI XUSUSIYATLARI VA MUALLIF TASVIR MAHORATI (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article analyzes the images of mothers in the major and minor prose works of Jadid writers and presents the artistic interpretations of these images in the works. The artistic skill of Jadid writers in creating the image of mothers is revealed.